[Rezension von: Helmut Lethen, Die Staatsräte. Elite im Dritten Reich: Gründgens, Furtwängler, Sauerbruch, Schmitt]Rowohlt, Berlin 2018. 351 S., € 24,–. - Kiesel, Helmuth (de Gruyter, 2021)
Helmut Lethen, Die Staatsräte. Elite im Dritten Reich: Gründgens, Furtwängler, Sauerbruch, Schmitt. Rowohlt, Berlin 2018. 351 S., € 24
In: Arbitrium, 39 (2021), Nr. 2. pp. 248-253. ISSN 0723-2977 (Druck-Ausg.), 1865-8849 (Online-Ausg)
Keywords: Rezension